2014
DOI: 10.1073/pnas.1410233111
|View full text |Cite
|
Sign up to set email alerts
|

Elevated hippocampal resting-state connectivity underlies deficient neurocognitive function in aging

Abstract: The brain is not idle during rest. Functional MRI (fMRI) studies have identified several resting-state networks, including the default mode network (DMN), which contains a set of cortical regions that interact with a hippocampus (HC) subsystem. Age-related alterations in the functional architecture of the DMN and HC may influence memory functions and possibly constitute a sensitive biomarker of forthcoming memory deficits. However, the exact form of DMN-HC alterations in aging and concomitant memory deficits i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
170
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(207 citation statements)
references
References 47 publications
29
170
4
Order By: Relevance
“…Although the findings reported here are not selective for the DMN, they parallel human studies demonstrating that the degree of temporal coupling between cortical and hippocampal DMN nodes in aging is associated with performance on tests of episodic memory (12,44). Considerable interest has centered on the network mechanisms that mediate this association.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although the findings reported here are not selective for the DMN, they parallel human studies demonstrating that the degree of temporal coupling between cortical and hippocampal DMN nodes in aging is associated with performance on tests of episodic memory (12,44). Considerable interest has centered on the network mechanisms that mediate this association.…”
Section: Discussionsupporting
confidence: 76%
“…Considerable interest has centered on the network mechanisms that mediate this association. In a recent study, Salami et al (44) reported that older, cognitively normal participants with increased FC between the left and right hippocampus exhibit a loss of associated FC along the anterior-posterior axis of the DMN, concomitant with poor episodic memory. The proposed account of these findings is that increased interhemispheric temporal coherence in the hippocampus disrupts interactions with neocortical components of a network critical for normal memory.…”
Section: Discussionmentioning
confidence: 99%
“…Associations were not controlled for age as a possible indirect driver of the correlations. (Salami, Pudas, & Nyberg, 2014) …”
Section: Multimodal Imaging Of Structural and Functional Connectivitymentioning
confidence: 99%
“…As noted by Tyszka et al (2011), morphological differences between AgCC and TD individuals are minimal on the lateral cortical surfaces, but are pronounced around the midline and ventricles due to the absence of the CC, and the presence of Probst bundles, mesial cortical reorganisation and colpocephaly. Therefore, we created a customised template using the DARTEL algorithm following the procedure outlined by Salami et al (2014), which is close to the procedure used by Tyszka et al (2011). First, individuals' T1-weighted images were segmented into grey and white matter using the toolbox "New Segment".…”
Section: Image Analysismentioning
confidence: 99%